THE ROLE OF MEDICAL TOURISM IN ATTRACTING FOREIGNERS - Eshonkulova Shakhnoza Abdujabbor kizi (TADQIQOTLAR, 2025)
Abstract: the article discusses the key factors that allow Uzbekistan to take a strong position in the international market of medical services, competing in the world community. The global trends in the development of tourism services and the possibilities of Uzbekistan to integrate into upward trends are being studied. The advantages of the natural potential of the country, the success of the medical industry in the implementation of state programs to attract medical tourists and encourage foreign investment are analyzed. The importance of using the experience of countries with developed medical tourism is emphasized.